A proposal for uniformity in classification of lymph node stations in esophageal cancer. Issue 10 (17th March 2021) - Schuring, N; Matsuda, S; Hagens, E R C; Sano, J; Mayanagi, S; Kawakubo, H; van Berge Henegouwen, M I; Kitagawa, Y; Gisbertz, S S
Summary: The 11 th edition of the "Japanese Classification of Esophageal Cancer" by the Japan Esophageal Society (JES) and the 8 th edition of the American Joint Committee on Cancer (AJCC)/Union for International Cancer Control (UICC) "Cancer Staging Manual" are two separate classification systems both widely used for the clinical and pathological staging of esophageal cancer. Furthermore, the lymph node stations from these classification systems are combined for research purposes in the multinational TIGER study, which investigates the distribution pattern of lymph node metastases. The existing classification systems greatly differ with regard to number, location and anatomical boundaries of locoregional lymph node stations. The differences in these classifications cause significant heterogeneity in studies on lymph node metastases in esophageal cancer. This makes data interpretation difficult and comparison of studies challenging. In this article, we propose a match for these two commonly used classification systems and additionally for the TIGER study classification, in order to be able to compare results of studies and exchange knowledge and to make steps towards one global uniform classification system for all patients with esophageal cancer.